Grisel's syndrome associated with mumps: A case report - Shen, Yanrong; Yang, Lixia; Liu, Xiaoliang; Xie, Yawen; Dai, Xiaohui; Wang, Chuan (Frontiers in Pediatrics, 2022)
Grisel's syndrome (GS) is defined as atlantoaxial rotatory subluxation/fixation not associated with trauma or bone disease, usually following head and neck infection/inflammation or ear, nose, and throat (ENT) surgery. Many conditions could lead to Grisel's syndrome, of which mumps is rarely to be seen. In this case, we reported a case of GS in children with Type I atlantoaxial joint subluxation and previously diagnosed mumps. A 6-year-old boy who had cervical pain and torticollis for two weeks was admitted to our hospital. He didn't suffer from trauma or ENT surgery, but was diagnosed with mumps two weeks ago due to swelling of the left cheek and cervical lymph node. Physical examination and computed tomography confirmed a diagnosis of Grisel's syndrome with an ADI (atlanto-dens interval) of 1.6 mm. The patient then received occipito-mandibular traction for six days and recovered. No recurrence was observed at one year's follow-up. Physicians should raise the awareness of this rare complication of mumps to avoid life-threatening neurological impairments owing to Grisel's syndrome.